Intraosseous Meningioma of the Frontal Bone: Management and Challenges in Autologous Bone Reconstruction - Lindner, Rafaela Jucá; Gibbon, Frederico de Lima; Vial, Antônio Delacy Martini (Indian Journal of Neurosurgery, 2025)
Intraosseous meningiomas, although uncommon, represent a distinctive and important subset of meningiomas. These slow-growing tumors arise from the arachnoid cells present in the meninges and infiltrate the adjacent bone, often presenting as palpable masses. This case report focuses on a female with a frontal bone intraosseous meningioma and its management and challenges, including autologous bone reconstruction (cranioplasty).
Keywords: bone reconstruction; cranioplasty; intraosseous meningioma